Manganese(II) complexes with thiosemicarbazones as potential anti-Mycobacterium tuberculosis agents - Oliveira, Carolina G.; Maia, Pedro Ivo da S.; Souza, Paula C. [UNESP]; Pavan, Fernando Rogério [UNESP]; Leite, Clarice Queico Fujimura [UNESP]; Viana, Rommel B.; Batista, Alzir A.; Nascimento, Otaciro R.; Deflon, Victor M. (Elsevier B.V., 2014)
Through a systematic variation on the structure of a series of manganese complexes derived from 2-acetylpyridine-N(4)-R-thiosemicarbazones (Hatc-R), structural features have been investigated with the aim of obtaining complexes with potent anti-Mycobacterium tuberculosis activity. The analytical methods used for characterization included FOR, EPR, UV-visible, elemental analysis, cyclic voltammetry, magnetic susceptibility measurement and single crystal X-ray diffractometry. Density functional theory (DFT) calculations were performed in order to evaluate the contribution of the thiosemicarbazonate ligands on the charge distribution of the complexes by changing the peripheral groups as well as to verify the Mn-donor atoms bond dissociation predisposition. The results obtained are consistent with the monoanionic N,N,S-tridentate coordination of the thiosemicarbazone ligands, resulting in octahedral complexes of the type [Mn(atc-R)(2)],paramagnetic in the extension of 5 unpaired electrons, whose EPR spectra are consistent for manganese(II). The electrochemical analyses show two nearly reversible processes, which are influenced by the peripheral substituent groups at the N4 position of the atc-R1- ligands. The minimal inhibitory concentration (MIC) of these compounds against M. tuberculosis as well as their in vitro cytotoxicity on VERO and J774A.1 cells (IC50) was determined in order to find their selectivity index (SI) (SI = IC50 / MIC). The results evidenced that the compounds described here can be considered as promising anti-M. tuberculosis agents, with SI values comparable or better than some commercial drugs available for the tuberculosis treatment.(c) 2013 Elsevier Inc. All rights reserved.
Keywords: Manganese(II); Thiosemicarbazones; Anti-Mycobacterium tuberculosis activity; Catalase peroxidase